ISU-ISU PENDIDIKAN DI INDONESIA - Sukari; Lalu Firman Hadiwijaya; Hafidz Abdul Rozaq (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Education is a fundamental pillar for national development. However, Indonesia’s education system continues to face multiple complex challenges. This article examines key issues in Indonesian education, including disparities in access between urban and rural areas, low learning quality as reflected in PISA results, frequent curriculum changes, and inadequate teacher competence and welfare. Moreover, globalization and technological advancement bring new challenges, such as digital inequality, weak digital literacy, and rising student mental health problems. Economic, political, socio-cultural, technological, and human resource factors, as well as links with industry, also influence education outcomes. Empirical data reveal high dropout rates, low readiness in implementing the Merdeka Curriculum, and high unemployment among vocational graduates. Several recommendations are proposed: ensuring equal access to education, improving curriculum quality, strengthening teacher competence and welfare, promoting inclusive digital transformation, reforming education governance, and reinforcing character education. Through comprehensive strategies, Indonesian education is expected to produce generations that are not only intellectually capable but also resilient, ethical, and globally competitive.